Correlation Between Peroxisome Proliferation and Up-Regulation of Cytochrome P450 CYP4A and Peroxisomal Beta-Oxidation Fatty Acyl CoA Oxidases (AOX) in the Koala (Phascolarctos Cinereus) - SNT Ngo, I Stupans and RA McKinnon (Gene expression to genetical genomics, 2010)
Peroxisomes are membrane bound cytoplasmic organelles that are involved in lipid metabolism and other biological functions. In rat and mouse, profound xenobiotic-induced peroxisome proliferation has been reported, with a marked increase in number and size of peroxisomes in liver parenchymal cells and induction of lipid metabolising enzymes, in particular cytochrome P450 CYP4A and peroxisomal β-oxidation palmitoyl CoA oxidases (AOX1). The present study investigates whether the previously observed higher hepatic CYP4A and AOX1 expression in the koala (Phascolarctos cinereus), a unique Australian marsupial, compared with rat and human is associated with peroxisome proliferation. Visualisation and quantification of peroxisomes were performed on liver samples from three koalas utilising transmission electron microscopy, with rat and bandicoot livers being used for comparative purposes. Numer- ous catalase positive peroxisomes, which clearly stand out by their black single membrane globular structures, were detected in all test ultra-thin sections from koala livers. A higher average number of peroxisomes per hepatocyte was observed for the koala, an obligate eucalyptus feeder, compared with non-eucalyptus feeders rat and bandicoot. No species differences in the average size of peroxisomes were detected. This is the first morphological study examining hepatic peroxisomes in an Australian marsupial. The results suggested that dietary eucalyptus constituents might possess peroxisome proliferating activities.